Morphology and Growth Test of Beauveria sp. of Rhizosphere in Sweet Guava - Fitriyah, Nilna Maulidatul; Susanti, Ambar (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Beauveria sp. is one of the fungi obtained from the exploration of the Rhizosphere in the Gondang Manis Guava plantation, which is located in the northern region of the Brantas River. This study aims to determine the morphology and growth of Beauveria sp. obtained from the exploration of endophytic fungi in the Rhizosphere of the Gondang Manis Guava plant. This research was conducted at the Agroecotechnology Laboratory, Faculty of Agriculture, KH University. A. Wahab Hasbullah, in vitro in April-July 2024, with qualitative and quantitative approaches, each with 5 replications. The results of the observation showed that the Beauveria sp. isolate had a yellowish white upper part, a bone white lower part, a zigzag colony shape spread out and a white powder hypha texture. The conidia of the fungus were hyaline in a round shape. The diameter after H-7 and H-14 was around 8 and 14 cm, respectively. Keywords: Beauveria sp; Gondang Manis Guava; Morfology